Detecting and mapping a CO2 plume with novel autonomous pH sensors on an underwater vehicle. (December 2021) - Monk, Samuel A.; Schaap, Allison; Hanz, Rudolf; Borisov, Sergey M.; Loucaides, Socratis; Arundell, Martin; Papadimitriou, Stathys; Walk, John; Tong, Daisy; Wyatt, James; Mowlem, Matthew
Highlights: Three novel pH sensors on an ROV mapped and quantified a pH drop from a CO2 release. The measured pH had high spatial gradients and was lowest within 2m of the seabed. The release rate was below the relevant detection limit for CCS yet was detected. The pH data were used to model the spatial extent of the CO2 plume. The model can aid selecting optimum sensor and vehicle pairing for plume detection. Abstract: We report the first successful use of chemical sensors integrated on to an underwater vehicle to locate, map and estimate flux from a controlled sub-seabed CO2 release, analogous to a leak from a Carbon Capture and Storage (CCS) reservoir. This has global implications for the efficacy and cost of monitoring of offshore CCS sites and hence public and regulatory confidence as this tool for addressing climate change is considered and rolled out. A remotely operated vehicle (ROV) equipped with three different pH sensors was deployed to determine the spatial extent of the controlled release. The sensors each operated on a different principle (spectrophotometric, fluorescence, and electrochemical) and the strengths and weaknesses of each sensor are discussed. The sensor data demonstrated that evidence of the plume was limited to within 3 m of the seafloor, as predicted by previous modelling work. The data were then utilised to develop a model of the plume, to extend the spatial coverage of the data. This comparison of the three sensors and the insight into plume dynamics provided by the model would assist in the planning of future plume surveys to ensure the sensor and vehicle combination can resolve the plume of interest.